2018
DOI: 10.1002/cptc.201800060
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Solution Phase Transient Absorption Study of the Plant Sunscreen Derivative Methyl Sinapate

Abstract: The plant sunscreen derivative methyl sinapate is studied in the gas-and solution-phase as an important step in understanding the structure-dynamics-function relationship of plant sunscreens such as sinapoyl malate. Results from gas-phase experiments suggest a three step deactivation process after photoexcitation. Photoexcitation to the S 1 state results in internal vibrational energy redistribution within 3 ps. Intersystem crossing then occurs in 30 ps between S 1 and T 1 and the latter state then persists ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 36 publications
4
51
0
Order By: Relevance
“…In the work by Zhao et al [ 111 ], the effect of para substituents on the excited-state photodynamics of MS (the trans - form) including para methoxy methyl sinapate ( p -OMeMS) and para hydrogen methyl sinapate ( p -HMS) shown in Figure 6 were investigated. Briefly, the findings revealed that p -OMeMS and MS undergo similar dynamics along the trans–cis photoisomerisation coordinate, as seen in previous studies [ 104 , 109 , 110 ]. p -HMS, on the other hand, undergoes different dynamics with an internal conversion from the initial optically bright excited state (denoted V(ππ*)) to a relative dark state (denoted V’(ππ*)), which results into branching of the excited-state relaxation.…”
Section: Case Studiessupporting
confidence: 79%
See 2 more Smart Citations
“…In the work by Zhao et al [ 111 ], the effect of para substituents on the excited-state photodynamics of MS (the trans - form) including para methoxy methyl sinapate ( p -OMeMS) and para hydrogen methyl sinapate ( p -HMS) shown in Figure 6 were investigated. Briefly, the findings revealed that p -OMeMS and MS undergo similar dynamics along the trans–cis photoisomerisation coordinate, as seen in previous studies [ 104 , 109 , 110 ]. p -HMS, on the other hand, undergoes different dynamics with an internal conversion from the initial optically bright excited state (denoted V(ππ*)) to a relative dark state (denoted V’(ππ*)), which results into branching of the excited-state relaxation.…”
Section: Case Studiessupporting
confidence: 79%
“…Building on the reported photodynamics for SM and SA ( Section 2.1.1 ), various sinapate ester derivatives that bridge the chemical complexity between these two have been studied in an attempt to design efficient plant-based UV filters for sunscreen formulation. TEAS and TD-DFT studies have been reported for methyl sinapate (MS), isopropyl sinapate (IS), sinapoyl methyl lactate (SML) and sinapoyl dimethyl malate (SDM) in various solvents and poly(vinyl alcohol) hydrogel film [ 104 , 109 , 110 ]. The results of these studies have been reviewed in more detail in previous publications [ 54 , 55 ].…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,[8][9][10][11][12] Recently, a number of studies have been carried out focussing on the photophysical properties of SM, specifically, how solution-phase SM photodeactivates after UV-B photoexcitation. [13][14][15][16] These point to SM (and similar derivatives [17][18][19][20] ) exhibiting a relaxation mechanism upon UV excitation involving ultrafast internal conversion from a photoexcited ππ* state to reform predominantly the original ground state trans-isomer, occurring along a trans-cis isomerisation reaction coordinate.…”
Section: Introductionmentioning
confidence: 99%
“…This relaxation mechanism, being mediated by the trans-cis isomerisation coordinate, is particularly interesting since it is readily observed in the solution phase and involves ππ* dynamics, whereas analogous gas-phase experiments involve significant nπ* dynamics and the different isomers are not readily distinguished. [15,[17][18][19]21,22] It is on this solution phase mechanism where this work focusses. We present transient absorption measurements of sinapoyl malate derivatives (Figure 1(A)) whose carboxyl groups are augmented to include increasingly large alkane chains to observe any changes to the trans-cis mediated relaxation pathway.…”
Section: Introductionmentioning
confidence: 99%